Financial Ratio Analysis As Instrument For Measuring Manufacturing Company Performance And Investment Decision Makaing On The Indonesia Stock Exchange (2019-2024) - Fitriani Rahim; Indah Lestari Anwar (International Journal of Education Management and Religion, 2026)
This study aims to analyze the effectiveness of financial ratios as instruments for measuring company performance and investment decision making in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. The novelty of this study lies in integrating the Environmental, Social, and Governance (ESG) dimension within a financial ratio analysis framework in the post pandemic context of Indonesian manufacturing. The research method is a descriptive quantitative approach with longitudinal comparative analysis of 50 purposively selected manufacturing companies from 222 IDX listed issuers, representing sub sectors of basic industries, various industries, and consumer goods. The financial ratios analyzed include liquidity ratios (current ratio, quick ratio, cash ratio), solvency ratios (debt to equity ratio, interest coverage ratio), profitability ratios (return on assets, return on equity, net profit margin, gross profit margin), activity ratios (asset turnover, inventory turnover, receivable turnover), and market ratios (pric to earnings ratio, price to book value). The results show a significant positive correlation between profitability ratios and firm value (r = 0.731; p < 0.01), while excessively high liquidity ratios are negatively correlated with investment returns. Practically, these findings offer strategic guidance for financial managers in optimizing liquidity-profitability balance, and for investors in prioritizing profitability ratios (ROE and NPM) as primary determinants of firm value in fundamental analysis